2013
DOI: 10.1177/0022034513506444
|View full text |Cite
|
Sign up to set email alerts
|

M180 Amelogenin Processed by MMP20 is Sufficient for Decussating Murine Enamel

Abstract: Amelogenin (AMELX) and matrix metalloproteinase-20 (MMP20) are essential for proper enamel development. Amelx and Mmp20 mutations cause amelogenesis imperfecta. MMP20, a protease secreted by ameloblasts, is responsible for processing enamel proteins, including AMELX, during the secretory stage of enamel formation. Of at least 16 different amelogenin splice products, the most abundant isoform found in murine ameloblasts and developing enamel is the M180 protein. To understand the role of MMP20 processing of M18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…In vitro studies have further shown that these mutations or deletion of the N-terminal conserved sequences lead to misfolding and uncontrolled aggregation of amelogenin [17,25,26]. The observation that the thin enamel seen in amelogenin knockout mice lacks prismatic-inter-prismatic architecture supports the notion that matrix-cell binding may be disturbed in the absence of amelogenin [27,28,29]. We suggest that, among other mechanisms, enamel malformation in cases of Amelogenesis Imperfecta with mutations at the amelogenin N-terminal may be the result of defective amelogenin-cell interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have further shown that these mutations or deletion of the N-terminal conserved sequences lead to misfolding and uncontrolled aggregation of amelogenin [17,25,26]. The observation that the thin enamel seen in amelogenin knockout mice lacks prismatic-inter-prismatic architecture supports the notion that matrix-cell binding may be disturbed in the absence of amelogenin [27,28,29]. We suggest that, among other mechanisms, enamel malformation in cases of Amelogenesis Imperfecta with mutations at the amelogenin N-terminal may be the result of defective amelogenin-cell interactions.…”
Section: Discussionmentioning
confidence: 99%
“…μCT was used to compare mineral densities of incisor and molar enamel in specific regions in CTRNCTg/LRAPTg/ Amelx −/− mice and controls. Adult mouse incisor and molar enamel were assessed for mineralization levels [29]. Hemimandibles with soft tissues removed were scanned in a μCT-40 (Scanco, Brüttisellen, Switzerland) at 70 kV, 114 mA, and 6 μm resolution.…”
Section: Methodsmentioning
confidence: 99%
“…Hemi-mandibles were embedded in plastic and polished longitudinally for scanning electron microscopy (SEM) analysis for enamel prism organization and enamel thickness [29]. Mandibles from 6 week-old male and female mice and controls were dissected, and erupted portions of mandibular incisors and molars were washed and dehydrated with graded alcohol and acetone, and embedded in Embed812 resin (Electron Microscopy Sciences, Hatfield, PA), ground in a sagittal plane, and polished to 0.25 μm with diamond suspensions (Electron Microscopy Sciences), etched with 0.1M phosphoric acid for 15 s, gold coated and imaged with a Zeiss Evo LS 10 SEM.…”
Section: Methodsmentioning
confidence: 99%
“…Mandibles were fixed overnight in 4% paraformaldehyde and prepared for analysis as described (Gibson et al, 2011) except that scans were performed on a microtomograph imaging system (μCT 40, Scanco Medical AG, Brüttisellen, Switzerland) with 16 μm resolution at 70 kVp (Pugach et al, 2013). The images were processed by three-dimensional reconstruction software (μCT Evaluation Program v6.0, Scanco Medical) and analyzed for enamel and dentin density and volume.…”
Section: Methodsmentioning
confidence: 99%